Transfer Teknologi Budidaya Tanaman Hias untuk Guru-Guru Biologi - P.K. Dewi Hayati; Warnita Warnita; Netti Herawati; Sutoyo Sutoyo; Martinius Martinius; Trizelia Trizelia; Herviyanti Herviyanti (Warta Pengabdian Andalas, 2019)
Cultivation of ornamental plants in the school is necessary to provide the loveliness, and conductive atmosphere and environment for the learning process in that school. This community empowerment program aimed to transfer knowledge and technology of ornamental plants cultivation, covering the aspects of growing media, application of plant growth regulator, propagation and hybridization of ornamental plants to the biology teachers of high school. The methods of empowerment were community learning, demonstration, training, and self-practice. Results from the activities showed that the representative biology teachers from districts and cities in West Sumatra could be understood and applied the techniques of ornamental plants cultivation in their respective schools. The Likert analysis showed that a percentage of 95.6%, indicating that the transfer of technology provided is very beneficial for high school biology teachers. Hence, this activity is needed to be continuous in the future.